2017
DOI: 10.1103/physrevlett.118.076801
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Excitations in the Fractional Quantum Hall Regime

Abstract: We study the minimal excitations of fractional quantum Hall edges, extending the notion of levitons to interacting systems. Using both perturbative and exact calculations, we show that they arise in response to a Lorentzian potential with quantized flux. They carry an integer charge, thus involving several Laughlin quasiparticles, and leave a Poissonian signature in a Hanbury Brown-Twiss partition noise measurement at low transparency. This makes them readily accessible experimentally, ultimately offering the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 46 publications
5
117
0
Order By: Relevance
“…In this direction, the characterization of a single‐quasiparticle source was recently proposed , and the HBT setup was studied in Ref. for Lorentzian WPs.…”
Section: Discussionmentioning
confidence: 99%
“…In this direction, the characterization of a single‐quasiparticle source was recently proposed , and the HBT setup was studied in Ref. for Lorentzian WPs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as shown in Ref. , it is mandatory that the total phase variation resulting from the voltage pulse is not a fraction of 2π in order to have only electron‐like excitations and thus a minimal excitation property. This implies that the Faraday flux, which in the 1/3 FQHE regime writes as e*Vfalse(tfalse)normaldt, must be equal to nh .…”
Section: Perspectivesmentioning
confidence: 99%
“…This situation has been studied in Ref. in a different spirit. In this regime, in agreement with predictions by , shot‐noise measurements, performed in a regime where only static dc voltage sources are used to create an incoming flux of integer charges, have shown that a Poissonian emission of fractional charges e* are emitted to contribute to the backscattering current .…”
Section: Perspectivesmentioning
confidence: 99%
“…In this case, screening currents may be generated at the quantum point contact level, which also lead to the kink smearing, but also to corrections to Eqs. (32) and (33). The most general capacitive coupling that also includes interactions between electrons inside and outside of the cavity is obtained by replacing Eq.…”
Section: Appendix D: Step Response With Finite Switching Time and Extmentioning
confidence: 99%
“…Operated out of equilibrium and in the weak tunneling limit, this system allows the triggered emission of single electrons [9][10][11] and has paved the way to the realization of quantum optics experiments with electrons [12][13][14][15], as well as probing electron fractionalization [16,17] and relaxation [18]. On-demand single-electron sources were also recently realized relying on real-time switching of tunnel barriers [19][20][21][22][23][24], "electron sound-wave surfing" [25][26][27], the generation of levitons [28][29][30][31][32], and superconducting turnstiles [33,34].…”
Section: Introductionmentioning
confidence: 99%